(3GdGbJUGO GdGaQjbi (B:s (3bVGjG GdJcGed hGdJfejI (B/s - (3aQL, aQL YHO GdaJGMs ((3GdbGgQI(B: s (3OGQ GdfgVI GdYQHjI(B, s, 2007)
(3jYGdL gPG GdcJGH Hjf OaJjg HMhKG aj eLGd GdJcGed hGdJfejI GdGbJUGOjI aj GaQjbjG hJe JbSjeg Edi KdGKI CbSGe GdbSe GdChd GdJcGed GdGbJUGOj hGdbSe GdKGfj bVGjG GdJfejI GdGaQjbjI hGdJfejI GdHTQjI HEYJHGQgG CMO Cge COhGJ JMbjb GdQaGgjI ddTYhH hNJe HbSe jYGdL eTcdGJ GdGbJUGO GdeUQj GdOjhf hGdGFJeGf GdeMdj hXGgQI GdGMJcGQ (B.s
(3edGMb hHjHdjhZQGajG fgGjI cd aUd s
Keywords: (3GbJUGO GaQjbjs; (3JcGeds; (3JfejIs